Use of crumb rubber as an additive in asphalt concrete mixture - Salih, Ahmed Rafid (2019)
As the rapidly growing number of vehicles in the world, the west of tire rubber becomes a major environmental concern. The use of crumb rubber in asphalt pavements has attracted increasing attention in many areas worldwide. Crumb rubber exhibits recycling potential as an additive or an alternative to natural resources used in pavement materials, as well as provides an effective approach to utilize waste products. The purpose of this study was to investigate the effect of adding crumb rubber to asphalt mixture using wet process and investigate the hardness and consistency of modified bitumen. The laboratory hot mix asphalt design tests were done by Marshall method procedure. In this study, two different crumb rubber contents (1% and 2% by weight of asphalt mixture) and two different size of crumb rubber (0.425mm and 0.150mm) were investigated. A comparative study was done among the unmodified and modified asphalt concrete mixtures considering the Marshall stability value and the resilient modules. The result showed that crumb rubber is recommended as an additive in asphalt mixture, as all the result are within the standard requirements. The addition of crumb rubber to asphalt concrete mixture tended to increase the strength and quality of asphalt mixture.